Perfil epidemiológico de pacientes diagnosticados com carcinoma epidermóide oral em Passo Fundo e região - Kuze, Luana Soares (2012)
Oral squamous cell carcinoma is a disease in most cases diagnosed in advanced stages which directly influences the prognosis of the case. The aim of this study was to evaluate the epidemiologycal, treatment and survival of patients diagnosed with oral squamous cell carcinoma at the Hospital São Vicente de Paulo of Passo Fundo-RS, which is a reference in the northern state of Rio Grande do Sul. Retrospective observational study was reformed, examining the records of patients diagnosed with this condition during the period from 1993 to 2008. Out of the 303 records analyzed, the majority were men (88.4%), caucasian (93.4%) with age racing from 51 to 60 years (37.0%). The association of alcohol and tobacco was observed in 84.7% of patients with cancer. The most affected site was the tongue (45.5%), but no difference was for the other regions in relation to survival (p = 0.201). Most cases observed were diagnosed in late stage III and IV (77.2%), with a survival of 17.83 months, showing difference for stages I and II (46.23 months, p = 0.003). Although surgical treatment has been the most performed (55.9%) and showed the no statistical survival, there was highest significance of this with the other treatments (p = 0.185). It was observed that 68.6% (n = 208) of patients died. It is the late diagnosis significantly decreased the life expectancy of patients (2.5 x), that the treatment performed and the initial location of the lesion had no significant influence on survival